The Caledonian Orogeny redefined - McKerrow, W; Mac Niocaill, C; Dewey, J (2000)
Recent advances in our understanding of Palaeozoic tectonics, and in the precise dating of tectonic events require exact definitions of terminology. The Caledonian Orogeny is here redefined to include all the Cambrian, Ordovician, Silurian and Devonian tectonic events associated with the development and closure of those parts of the Iapetus Ocean, which were situated between Laurentia (to the NW) and Baltica and Avalonia (to the SE and east). We suggest that the term 'Caledonian Orogeny' be restricted in this geographic sense, but that (as in modern usage) it continues to encompass a series of tectonic, or orogenic, phase (related to arc-arc, arc-continent and continent-continent collisions as Iapetus was closing). Many of these phases have been named; these and many more unnamed events are defined as orogenic phases (local components) of the Caledonian Orogeny. Some of these phases were synchronous over long distances, whereas others were diachronous. The whole Caledonian Orogeny occupied a time interval of around 200 Ma. Thus the term Caledonian should not be used to indicate age.